A sociolinguistic consideration of free and open source software teams as virtual communities of practice - Freudberg, Jeremy (Lingua Frankly, 2018)
A sociolinguistic exploration of free and open source software (FOSS) development teams as virtual communities of practice will offer further conclusions about the identity of these groups and their relevance to linguistic inquiry. Making use of the "third wave" notion of style laid out by Eckert (2012), it is revealed how a FOSS community may make use of certain language norms to cement their identity both against their opponent of proprietary software groups and within the larger spheres of the Internet.